Superoxide Dismutase 3 Controls the Activation and Differentiation of CD4+T Cells - Agrahari, Gaurav; Sah, Shyam Kishor; Bang, Chul Hwan; Kim, Yeong Ho; Kim, Tae-Yoon (Frontiers in Immunology, 2021)
Superoxide dismutase 3 (SOD3), a well-known antioxidant has been shown to possess immunomodulatory properties through inhibition of T cell differentiation. However, the underlying inhibitory mechanism of SOD3 on T cell differentiation is not well understood. In this study, we investigated the effect of SOD3 on anti-CD3/CD28- or phorbol myristate acetate (PMA) and ionomycin (ION)-mediated activation of mouse naive CD4+ T cells. Our data showed that SOD3 suppressed the expression of activation-induced surface receptor proteins such as CD25, and CD69, and cytokine production. Similarly, SOD3 was found to reduce CD4+T cells proliferation and suppress the activation of downstream pathways such as ERK, p38, and NF-κB. Moreover, naïve CD4+T cells isolated from global SOD3 knock-out mice showed higher expression of CD25, CD69, and CD71, IL-2 production, proliferation, and downstream signals compared to wild-type CD4+T cells. Whereas, the use of DETCA, a known inhibitor of SOD3 activity, found to nullify the inhibitory effect of SOD3 on CD4+T cell activation of both SOD3 KO and wild-type mice. Furthermore, the expression of surface receptor proteins, IL-2 production, and downstream signals were also reduced in Th2 and Th17 differentiated cells upon SOD3 treatment. Overall, our data showed that SOD3 can attenuate CD4+T cell activation through modulation of the downstream signaling pathway and restrict CD4+T cell differentiation. Therefore, SOD3 can be a promising therapeutic for T cell-mediated disorders.